How Central Sulawesi Province's Natural Disasters Affect Economic Growth? - Rasidin Karo Karo Sitepu; Rama Mahesa; Arief Maulana; Mhd. Asaad (Jurnal Ekonomi Pembangunan, 2023)
Historically, Indonesia is an area prone to natural disasters. Potential losses caused by natural disasters can be death, injury, illness, threatened life, sense of security, displacement, damage or loss of objects, and disruption of daily activities. The impact of natural disasters will indirectly affect output, income, demand for labor, and economic growth. This study aims to calculate the impact of natural disasters in Central Sulawesi Province (which occurred in 2018) on the regional and national economies. The method used is the Interregional Input-Output model measuring 17 sectors and 34 provinces. The findings show that Central Sulawesi Province's Gross Regional Domestic Product is IDR.114.01 trillion, decreased-12.93 percent to IDR.99.27 trillion due to natural disasters. Labor demand decreased by -9.68 percent, and income decreased by -9.58 percent. Natural disasters in Central Sulawesi Province also impacted the decline in National GDP by -0.16 percent. Disaster mitigation programs are essential for anticipating direct and indirect losses caused by natural disasters. Consequently, the government must consider the impact of inflation and economic growth when implementing disaster mitigation programs on the public agenda.